(untitled) (Sindoro: Cendikia Pendidikan, 2025)
Character education is a variety of efforts made in order to improve the character of children, especially students of MA Tabana Montong. So that they become whole and characterful human beings in the dimensions of heart, mind, body, feeling and will. Character education is the best solution in order to form and strengthen the character of the nation which then becomes a moral human being and is able to fortify itself from the current rapid globalization. Character education in Islamic teachings is always carried out since childhood, one of which is by getting used to praying dhuha and morning studies. Character building through the habit of praying dhuha and morning studies is a character education that seeks to form the character and morals of children so that they are protected from moral degradation in the form of thoughts and behavior. So in this study will examine the Effectiveness of the Habit of Praying Dhuha and Morning Studies in Improving Student Character at Madrasah Aliyah Tarbiyatul Banin Banat (MA TABANA) Montong. This study aims to describe the Effectiveness of the Habit of Dhuha Prayer and Morning Study in Improving Student Character at Madrasah Aliyah Tarbiyatul Banin Banat (MA TABANA) Montong. The method used in this study is qualitative descriptive research. In collecting data in the field using observation, interview and documentation techniques.